Variation of oil content and fatty acid composition of Millettia pinnata (L.) progenies in Tamil Nadu: VARIATION OF OIL CONTENT AND FATTY ACID COMPOSITION OF MILLETTIA PINNATA PROGENIES - B PALANIKUMARAN; K T PARTHIBAN; R JUDE SUDHAGAR; S VENNILA (Journal of Oilseeds Research, 2016)
Thirty progenies of Millettia pinnata commonly known as ’Pungam’ were studied for seed, oil quality as well as fatty acid profile. Among the progenies, only one progeny viz., FCRIMP 2 consistently expressed superiority in all seed characteristics viz., pod length (5.56 cm), pod width (2.98 cm), seed length (2.81 cm), seed width (2.20 cm), 100-seed weight (129.63 g), germination per cent (89.67%), germination value (11.07), peak value (3.45) and oil content (37.50 %). Among the thirtyprogenies, only nine progenies viz., FCRIMP 2 (37.50%), FCRIMP 3 (33.50%), FCRIMP 4 (37.50%), FCRIMP 6 (33.50%), FCRIMP 12 (34.50%), FCRIMP 15 (35.50%), FCRIMP 22 (34.50%), FCRIMP 24 (33.50%) and FCRIMP 25 (35.50%) recorded higher oil content. The analysis offatty acid composition revealed that the major fatty acid was oleic acid (12.02 to 12.39%) followed by palmitic acid (1.30-2.65%) and stearic acid (0.12-0.68%).